The Effect of Green Recruitment and Green Training on Employee Sustainable Performance Through Employee Green Behavior (A Study of Educational Staff at Mercu Buana University, Jakarta) - Kholilah Kholilah; Suprapto Suprapto (International Journal Labs, 2026)
Improving sustainable performance is now a strategic issue for various organizations, including universities, alongside increasing demands for efficient resource utilization and environmental concern. In the realm of human resource management, the implementation of Green Human Resource Management (Green HRM) is understood as a strategy that has the potential to strengthen sustainable performance through environmentally oriented human resource practices. At Mercu Buana University, efforts have been made to improve the performance of education personnel, but the results achieved are still not optimal. Therefore, this study aims to examine the influence of Green Recruitment and Green Training on Employee Sustainable Performance with Employee Green Behavior as a mediating variable among the education staff of Mercu Buana University Jakarta. With a population of education personnel and a sample of 163 respondents, data analysis was conducted using the SEM-PLS method. The results of the study found that: Green Recruitment does not have a significant effect on Employee Sustainable Performance; Green Training does not have a significant effect on Employee Sustainable Performance; Employee Green Behavior has a significant effect on Employee Sustainable Performance; Green Training has a significant effect on Employee Green Behavior; the indirect influence of Green Recruitment on Employee Sustainable Performance through Employee Green Behavior has a positive and significant effect; and the indirect influence of Green Training on Employee Sustainable Performance through Employee Green Behavior has a positive and significant effect.